Effect of Lecanicillium lecanii (zimm) and Beauveria bassiana (bals.) About Panonychus citri - Erika Paola Alayo-Aguirrea (2017)
It was determined the effect of Lecanicillium lecanii (Zimm) and Beauveria bassiana (Bals.) On the phytophagous mite Panonychus citri. For this, the breeding of P. citri was carried out, and it was propagated to both fungi in potato sucrose agar. Five treatments were performed with three replicates each; each treatment had 30 specimens between nymphs and adults of P. citri and the technique of inoculation was by spray. At the first treatment, 0.1% tween 80 was inoculated; at the second and third treatments, L. lecanii were applied at concentrations of 106 and 107 conidia / mL respectively; and at the fourth and fifth treatments, B. bassiana was applied at 106 and 107 conidia / mL respectively, and the specimens were incubated at room temperature until symptoms appeared to be slow moving, tegument darkening, dehydration and death. Dead mites were placed in a humid chamber until the appearance of mycelium, which was isolated on sucrose potato agar with antibiotic for microscopic observation and identification. It was found that the lowest percentage of P. citri survival was compared to B. bassiana with 17% and 6% at the concentrations of 106 con / mL and 107 con / mL, with a significant difference; Whereas with L. lecanii the survival rate was 29% and 20% at the concentrations of 106 con/ mL and 107 con/ mL, with no significant difference between the two concentrations. It was concluded that B. bassiana and L. lecanii have an entomopathogenic effect on the nymphs and adults of P. citri; obtaining a lower percentage of mite survival by increasing the concentration of B. bassiana conidia while in L. lecanii the two concentrations of conidia have the same entomopathogenic effect on the nymphs and adults of P. citri